Human rights and domestic implementation mechanism - Rahman, Mizanur, 1956-; Empowerment Through Law of the Common People (Dhaka : Empowerment Through Law of the Common People, 2006)
With reference to Bangladesh.
Includes bibliographical references.
Keywords: Human rights -- Bangladesh